The argumentative dimension of simile and illustrative analogy and their applications in Prophetic Hadith - DAHMANI, Hamza; KHALDI, Hichem; BENYAHIA, Fatiha (The International tax journal, 2025)
Argumentation is a key component of pragmatic theory, as it shapes discourse in a persuasive manner that influences the interlocutor and convinces them of the content of the message. Among the rhetorical devices that intertwine rhetoric with argumentation is the simile, which brings meaning closer to the listener's mind by representing it through sensory images drawn from reality. These images can embody and stabilize that meaning. Thus, simile constitutes a specific technique whose persuasive effectiveness lies in the considerable argumentative force it provides, exceeding its merely aesthetic value. It is capable of stirring the recipient, engaging their thinking, and prompting them to generate and construct the meanings of texts. This study has therefore been selected to investigate and analyse several forms of argumentative simile found in the Prophetic Hadith.